Kekerasan dalam Mendisiplinkan Anak: Telaah Batasan dan Celah dalam Pertanggungjawaban Pidana di Indonesia - Febrina Hertika Rani; Samsul Samsul; Rd. Muhammad Ikhsan; Dea Justicia Ardha (CV. Doki Course and Training, 2025)
In Indonesian positive law, the prohibition of all forms of child abuse is not only present as a legal norm, but also as a moral commitment of the state to guarantee the dignity and safety of children. However, the reality on the ground shows that violence against children still often occurs in closed domestic spaces. Some of these acts are justified on the grounds of discipline, as if the use of physical violence were a legitimate tool in the parenting process. This study aims to identify and understand the precise limits of physical violence that is justified as child discipline under Indonesian positive law and to determine whether there are legal loopholes that allow parental violence in the context of discipline to go unpunished. This study uses normative legal research, an approach that centres legal texts and norms. Indonesian positive law, in principle, prohibits all forms of violence against children. However, the regulations do not provide a clear limit on which disciplinary actions remain justifiable. In other words, the legal boundaries exist normatively, but are not explicitly and operationally articulated so that they can be easily applied in practice. When these provisions are applied in practice, it is clear that there are still significant ambiguities and legal loopholes, namely, the absence of a definition or limitation of discipline in positive law. The existence of room for subjective interpretation by officials and judges. Socio-cultural constructs that still legitimise corporal punishment. The linking of violent offences to the element of injury, so that 'minor' violence often goes unpunished. The absence of explicit norms prohibiting physical violence as a form of child discipline. The lack of consistent law enforcement guidelines and jurisprudence. It is this law that opens up the possibility of impunity, namely, the suboptimal criminal accountability of perpetrators of violence who hide behind the excuse of discipline.